Beyond Traditional Methods of Judicial Interpretation and Adaptation - Mohamed Injar (European Scientific Journal, ESJ, 2026)
The impact of the unforeseen on “economy of the contract” is a practical problem, where the unexpected event destroys the economic balance negotiated by the parties. To mitigate this, the contracting entities include adaptation clauses, designed to safeguard the internal economy of the contract. However, most of these mechanisms are poorly drafted, often leading to disputes regarding their true meaning. Consequently, the choice of the interpretive method by the judge, the lens through which he is going to use to read the clauses, has a major impact on how he enforces them. Traditional interpretative methods tend to treat the contract as a static text or subjective puzzle, resulting in judgments that are legally correct but economically absurd, which led some judges to adopt an economic method that treats the contract as an economy. This point highlights the central challenge that this paper addresses: To what extent does the economic method outperform traditional approaches in enhancing accuracy, reducing unpredictability of outcomes when courts interpret and enforce adaptation clauses? Methodologically, this study employs a dual approach: it combines a critical doctrinal analysis, utilizing a comparative review to illustrate divergent outcomes, and a normative Law and Economics framework. This framework explains why the "economy of the contract" is a superior method, offering a direct practical outcome by enhancing both fairness and predictability in judicial decisions. Consequently, this paper contributes to critical debates regarding the failure of traditional methods, arguing that their rigid application often precipitates the economic destruction of the agreement.